Electrophysiological subtypes and associated prognosis factors of Mexican adults diagnosed with guillain-barré syndrome, a single center experience. (April 2021) - López-Hernández, J.C.; Colunga-Lozano, L.E.; Galnares-Olalde, J.A.; Vargas-Cañas, E.S.
Highlights: In our univariate assessment we identified several predictors related with an unfavorable outcome (diarrhea, mechanical ventilation, Hughes score, MRC score, pure motor clinical variant and AMAN subtype). Factors such as age, or severe axonal damage can be risk factors for prolonged mechanical ventilation, which would independently affect the functional prognosis. Miller-Fisher syndrome (MFS) and MFS/Overlap variants comprise 13.9% of our patients. Throughout clinical experience and literature reports, patients with MFS and MFS/Overlap variants have good functional outcomes.